Bimbingan dan Konseling Sebagai Bagian Dari Pendidikan Islam - Fitriyani (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Guidance and Counseling is part of Education. Education and Guidance Counseling are two activities carried out in educational institutions, both formal education and non-formal education. Likewise in Islamic education, guidance and counseling is one of the topics discussed in it. Because guidance and counseling are also found in Islamic teachings which originate from the Al-Qur'an and Hadith. Not a few of the general public think that education and counseling are different, especially if they are linked to Islam. Apart from that, slanted expressions and views about Guidance and Counseling are increasingly spreading, so that their existence in several regions in Indonesia is considered completely meaningless, especially when linked to Islamic Education. Therefore, this series of articles will examine thematically between the two as a form of command/prohibition and cooperation so that awareness of the desire and recognition of Guidance and Counseling activities as one of the Islamic Education Efforts can be felt by the community.